Agama dan islam: Islam Sebagai Doktrin Dan Peradaban Dalam Menangkal Radikalisme - Nur Laila Rahmawati (Attanwir : Jurnal Keislaman dan Pendidikan, 2020)
Islamic education could not be denied being influenced by the renewal of Western model education. The case of Ahmad Dahlan and Wahab Khasbullah can be an example of how the modernization of education through Western models carries the consequences of changing Islamic education in Indonesia. Kuntowijoyo expressed the fact that the newly born Muhammadiyah actually faced 3 fronts, namely traditionalism (Pesantren and Kiyai), Jawaism (animism and dynamism) and modernism (Dutch colonization). Kiayi Dahlan as the leader of Muhammadiyah asserted that the retardation faced by Muslims in the early XX century as a result of ignorance therefore education has an important role to overcome. The basic value that must be enforced to mjembangun a nation is a moral education based on the Qur'an hadith, a balanced individual education between physical and spiritual needs and social education to foster the ability and usefulness of living in society. Muhammadiyah is establishment of modern Madrasah not only for men but also women who in those days is a taboo and the establishment of a school of modern teachers and there are payroll teachers who at that time pay the cost of illegal education because it is considered that the science of unbiased traded. The interaction between students, teachers, and the public is very important meaning for the development of Muhammadiyah education and in relation to the school teachers/lecturers of Muhammadiyah colleges is the key holder of the success of Muhammadiyah Education.